Peran Psikiater Dalam Pembuktian Kekerasan Psikis Pada Korban Tindak Pidana Kekerasan Dalam Rumah Tangga - Erwin Asmadi (DE LEGA LATA: JURNAL ILMU HUKUM, 2018)
The harmonious relationship of the household is the dream of every human being. But in the journey of the household ark, there are obstacles such as violence. If the violence is carried out physically or sexually, then there are injuries or signs that can be seen in plain view. But if the violence hits someone psychologically, it requires special knowledge to identify the existence of psychological violence suffered by victims of domestic violence. This paper outlines the important role of psychiatrists in proving psychological violence in criminal acts of domestic violence. Based on the provisions of Article 184 paragraph (1) letter b of the Criminal Procedure Code, the role of the psychiatrist who provides information as an expert is located as an expert so that it becomes one of the evidences. Another role, psychiatrists can publish Visum et Repertum known in the world of psychiatrists as Visum et Repertum Pshiciatricum.